2022
DOI: 10.1038/s41467-021-27647-0
|View full text |Cite
|
Sign up to set email alerts
|

Latency reversal plus natural killer cells diminish HIV reservoir in vivo

Abstract: HIV is difficult to eradicate due to the persistence of a long-lived reservoir of latently infected cells. Previous studies have shown that natural killer cells are important to inhibiting HIV infection, but it is unclear whether the administration of natural killer cells can reduce rebound viremia when anti-retroviral therapy is discontinued. Here we show the administration of allogeneic human peripheral blood natural killer cells delays viral rebound following interruption of anti-retroviral therapy in human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 61 publications
2
47
0
Order By: Relevance
“…In HIV-1 infected humanized mice, ILC1 and ILC3 are depleted in lymphoid tissues by type 1 IFN produced by pDCs ( 59 , 60 ). Recently, Kim and colleagues ( 89 ) demonstrated that infusion of allogenic human NK cells in HIV-1-infected humanized mice can delay HIV-1 viral rebound after ART interruption. Additionally, animals who received allogenic NK cell transfer displayed reduced diversity in HIV-1 species, highlighting the significance of NK cells in HIV-1 control in this model.…”
Section: Animal Models For Hiv-1 Elite Controllersmentioning
confidence: 99%
“…In HIV-1 infected humanized mice, ILC1 and ILC3 are depleted in lymphoid tissues by type 1 IFN produced by pDCs ( 59 , 60 ). Recently, Kim and colleagues ( 89 ) demonstrated that infusion of allogenic human NK cells in HIV-1-infected humanized mice can delay HIV-1 viral rebound after ART interruption. Additionally, animals who received allogenic NK cell transfer displayed reduced diversity in HIV-1 species, highlighting the significance of NK cells in HIV-1 control in this model.…”
Section: Animal Models For Hiv-1 Elite Controllersmentioning
confidence: 99%
“…sesterterpenoid, ansellone J ( 6 ), was further evaluated for HIV latency reversal in a primary cell context using CD4+ T cells obtained directly from four cART-suppressed donors with HIV (Figure ). Ansellone J ( 6 ) induced HIV latency reversal at levels similar to prostratin ( 3 ) ex vivo , but at a 10-fold lower concentration, making 6 a promising lead compound for the development of synthetic LRAs as clinical trial candidates to test the potential of a “shock and kill” approach to a sterilizing cure for HIV-1 infections …”
Section: Resultsmentioning
confidence: 99%
“…Administration of allogeneic human peripheral blood NK cells delayed viral rebound following interruption of ART in humanized mice infected with HIV-1. 72 A kick and kill strategy comprised of the protein kinase C modulator SUW133 and allogeneic human peripheral blood NK cells during ART eliminated the viral reservoir in a subset of these mice. SMU-Z1, a novel small-molecule TLR1/2 agonist enhanced HIV-1 transcription and promoted NK cell-mediated inhibition of HIV-1 infected autologous CD4 + T cells.…”
Section: Challenges In Anti-hiv-1 Car Cell Therapy For Immune Surveil...mentioning
confidence: 99%